2017
DOI: 10.1002/mrm.26832
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of the approximation of diffusion‐weighted‐MRI signals from crossing fascicles by sums of signals from single fascicles

Abstract: The use of the superposition approximation rather than a model of interwoven fascicles does not adversely impact the estimation of microstructural features of interwoven fascicles in most current clinical settings. Magn Reson Med 79:2332-2345, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In addition, we found that simulations substrates with less than 10,000 sampled cylinders induced an important bias on the directional symmetry of the diffusion signal in directions transversal to the the main fiber direction. Such parameters are almost one order of magnitude bigger than previously used on the literature, which inherently affects the reproducibility of such results [39,40,2,21]. Second, our evaluation over the effect of introducing angular perturbations in the intra-axonal space representation-by means of the estimated axon diameter based on the cylindrical model-showed a considerable deviation from the expected results.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, we found that simulations substrates with less than 10,000 sampled cylinders induced an important bias on the directional symmetry of the diffusion signal in directions transversal to the the main fiber direction. Such parameters are almost one order of magnitude bigger than previously used on the literature, which inherently affects the reproducibility of such results [39,40,2,21]. Second, our evaluation over the effect of introducing angular perturbations in the intra-axonal space representation-by means of the estimated axon diameter based on the cylindrical model-showed a considerable deviation from the expected results.…”
Section: Discussionmentioning
confidence: 68%
“…[6][7][8][9] In the context of dMRI, the measured signal  probes diffusion processes over a specific observational time-scale that depends on the choice of experimental time parameters. For a given observational time-scale, a common description of the subvoxel composition of heterogeneous tissues is obtained by considering the combined non-Gaussian diffusion effects of restriction and exchange and approximating the signal decay by a continuous weighted sum of exponential decays, 6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] yielding the following multidimensional Laplace transform:…”
mentioning
confidence: 99%
“…Numerical simulations can help deepen the understanding of the relationship between the cellular structure and the diffusion magnetic resonance imaging signal and lead to the formulation of appropriate models. They can be also used to investigate the effect of different pulse sequences and tissue features on the measured signal which can be used for the development, testing, and optimization of novel diffusion magnetic resonance imaging pulse sequences [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%